Surgical system resilience in armed conflict: ensuring continuity of essential surgical care - Nadav Grinberg; Reema Mahmoud; Oren Peleg (Perioperative Medicine, 2026)
Abstract Background Armed conflict poses a growing threat to the continuity of essential health services worldwide. While preparedness frameworks often focus on trauma response and emergency medicine, considerably less attention has been given to maintaining routine and urgent surgical care during prolonged security crises. Surgical services are essential components of health systems, addressing trauma, oncologic disease, infections, obstetric emergencies, and complications of non-communicable diseases. Disruptions to surgical care, therefore, carry substantial indirect health consequences that extend beyond the immediate injuries of conflict. Main body This perspective examines the concept of surgical system resilience- the capacity of health systems to maintain surgical services during crisis conditions. Drawing on recent experiences from hospitals operating under missile attacks in Israel, we describe operational adaptations that enabled the continuation of surgical services despite ongoing security threats. These adaptations included the rapid relocation of clinical services to protected underground hospital infrastructure, modification of surgical workflows, and strengthened multidisciplinary coordination across clinical departments. Maintaining surgical services during conflict requires balancing trauma preparedness with the ongoing treatment of urgent non-traumatic surgical conditions. The experience highlights several domains that contribute to surgical system resilience, including protected infrastructure, operational flexibility, workforce preparedness, and coordinated institutional leadership. Conclusion Ensuring the continuity of surgical care during armed conflict is a critical component of health system resilience. Lessons from Israeli hospital preparedness may inform policy strategies aimed at strengthening surgical system resilience in other regions facing security threats or large-scale disruptions.